ANALYSIS OF SMALLHOLDER TOMATO FARMERS AWARENESS AND ADOPTION OF ICT-BASED PEST INFORMATION SERVICES IN THE CENTRAL HIGHLANDS OF KENYA - MWENDA, EVANS (MksU Press, 2022)
Tomato is a widely consumed vegetable in Kenya and globally. It is an essential source of nutrients, income and employment. Pest infestation is one of the major challenges in tomato farming that leads to low- and poor-quality production especially through physical destruction of the products and high production cost due to their control measures. Besides, tomato farmers experience difficulties in accessing timely pest information to enable effective pest management decisions. Use of Information and Communication Technology (ICT) is a novel pathway of helping farmers to access pest information services, particularly in an environment with declining public extension services. However, there is scanty literature on awareness and adoption levels of ICT-based pest information services by farmers, together with the factors that limit adoption of these services by farmers. Available studies give mixed results on factors influencing adoption of ICT-based information services. The main objective of this study was to analyze tomato farmers‟ awareness and adoption of ICT-based pest information services in tomato production in the Central Highlands of Kenya. Specifically, the study: (i) characterized the current information services for tomato pests and their management, (ii) assessed the farmer awareness and adoption of ICT-based pest information services and (iii) assessed the determinants of and factors limiting the adoption of ICT-based pest information services. The study was conducted in Nyeri and Meru Counties. Data was collected between October and November, 2021, through field surveys using structured questionnaires, which were administered by trained enumerators to a sample of 170 farmers using KoBo Toolkit. The data was analyzed using descriptive statistics, inferential statistics and Logistic Regression. The results indicate that the current sources of agricultural pest information were ICT-based and non-ICT-based. The main non-ICT based sources were; other farmers (82.9%), agro dealers (81%), public extension officers (47%) and agro chemicals‟ sales agents (30%). The ICT-based sources were radio programs (94%), television programs (90%) and mobile- and internet-based information services (MIBIS) (100%). Farmers reported high awareness of ICT-based information services, with 100% awareness of radio programs, 93% TV programs and 83% MIBIS. However, the adoption rate was low as only 48% of the farmers adopted at least one ICT-based information service. The most adopted service was radio programs (34% adoption rate) followed by television programs (30%) and MIBIS (28%). The study found that the factors that positively influenced adoption of ICTbased pest information services were: gender (male), membership in social groups, off-farm employment, levels of trust on ICT-based information sources, transport costs to nearby market centers and area under tomato production. The factors that had a negative influence on adoption were; the level of education, size of land owned, and the production system, with greenhouse system having lower adoption level than open field system. Factors limiting ICT-based pest information services adoption include: poor timing of the information broadcast by service providers; lack of ownership of ICT tools and high cost of using the services. The results from this study provide unique evidence to inform policymakers on the need to integrate ICT-based tools into strategies and interventions for disseminating pest information services to farmers. The findings suggest that the radio and television service providers should air information at the most convenient times for farmers, who prefer evening broadcasts. There is also a need to encourage farmers to form and participate in social groups and cooperatives that support adoption of ICT-based pest information services. Further studies can be done to evaluate the impact of ICT-based pest information services on pest management, productivity and profitability of tomato production.